Coopetition and symbiosis: Revisiting two buzzwords of the "innovation ecosystem" metaphor - Ulrich Klüh (Hochschule Darmstadt, Fachbereich Wirtschaft, Zentrum für Nachhaltige Wirtschafts- und Unternehmenspolitik ZNWU, 2022)
Should we be more critical and nuanced when it comes to the metaphorical, notional and representational worlds that define innovation ecosystem? Through a deconstruction of two important ecosystem metaphor, we reveal a pronounced disaccord between the normative charge of respective notions on the one hand, and the potential realities implied by more critical research. However, we do not call for a complete abolishment of the ecosystem metaphor, for three reasons: First, the literature is developing quickly, and becoming more nuanced and aware of its limitations. It should have a chance to develop and to take on board criticism, such as one on hand. Second, even though we find many reasons to believe that existing metaphors, notions and representations might lead policymakers to look exactly in the wrong direction, and to underestimate the risks associated with (innovation) ecosystems, the term itself is here to stay, at least for the foreseeable future. Political actors have to live with it, by changing the way it is used and understood, and by taking a more radical approach towards implementation and regulation, taking into account the fact that the structures we call "ecosystems" in the business context are small and rather unimportant elements of larger ecosystems. Third, and finally, we believe that a key challenge of coming years is to find technical solutions to ecological problems without falling into the trap of a belief in technofixes. While the main transformative questions are political and distributive, technology will need to play a role, and we need terms that open an arena for agonistic struggles about this role. Ecosystem terminology might play a role in this respect.
Keywords: 330; innovation; ecosystem; coopetition; symbiosis